Influence of coating structure of an SiOx barrier coating on a PET substrate on water vapor permeation activation energy (2024)
The application of plasma polymerized silicon-based coatings on plastic substrates is an effective way to adjust the permeability of the substrate. However, the permeation mechanisms are yet not fully understood. Here, the activation energy of permeation can offer valuable insights. In order to understand how the activation energy of permeation depends on the coating structure, five silicon-based coatings with varying oxygen content were analyzed, which led to property modifications ranging from silicon-oxidic to silicon-organic. Positron annihilation spectroscopy was employed to characterize the free volume and quartz crystal microbalance measurements were used to determine the density of the coating. These results were compared to water vapor permeation measurements with a temperature variation in the range of 15°C to 50°C. As expected, the silicon-organic coatings do not significantly impact the permeation rates, while the silicon-oxidic coatings do exhibit a barrier effect. The density of the coatings increases for the more silicon-oxidic coatings. A coating with an unusually high oxygen to precursor ratio forms the exception in both permeation and density. The free volume appears to increase for the more silicon-organic coatings. The pore wall chemistry is also affected, hinting at a structural transition from silicon-organic to silicon-oxidic. With this approach, we aim for an in-depth understanding of the chemical structure of silicon-based thin film coatings and its influence on gas permeation through those coatings.